Reconstructing Ukrainian Identity: The Impact of the Russian-Ukrainian War Trauma - Kushch, Elina (Dia-noesis: A Journal of Philosophy, 2025)
The paper explores the reconstruction of the Ukrainian national identity in the context of the traumatic events of the Russian-Ukrainian war. The war traumatic experience is viewed as a source of suffering and existential challenges for Ukrainians and a catalyst for constructing their renewed collective “we”. This involves rethinking the history of the Ukrainian nation, its social, political, and cultural heritage. The paper also focuses on the development and the role of the Ukrainian language, the emergence and spread of various verbal and nonverbal initiatives and practices that contribute to overcoming the collective war trauma and revitalizing the image of Ukrainians as a nation in the world.